CIVIL LIABILITY OF PHARMACEUTICAL MANUFACTURING COMPANIES UNDER ALGERIAN LEGISLATION – A COMPARATIVE STUDY - Benyagoub Abdenour (International Journal of Innovative Technologies in Social Science, 2024)
This study aims to examine the civil liability borne by pharmaceutical production companies when their activity results in causing harm to the drug consumer. The interest in this subject is due to the special nature of the medicine, as it is a product inseparable from human health, which makes any defect affecting it a possible cause of serious damage. It is observed in this field that the consumer is often not bound by a direct contractual relationship with the drug producer, but rather obtains the medicine through the pharmacist, which raises the problem of determining the legal basis of liability. From this perspective, the study addresses the forms of civil liability of pharmaceutical production companies, between contractual liability and tort liability, while also stopping at the tendency toward recognizing an objective liability that arises merely upon the occurrence of damage. The study also relies on a comparison between Algerian legislation and both Jordanian and French legislations, in order to assess the adequacy of the current legal rules in protecting the drug consumer and repairing the damage that may be inflicted upon him.